2007
DOI: 10.2106/jbjs.f.01292
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Systematic Reviews of Anterior Cruciate Ligament Reconstruction Comparing Hamstring Autograft with Bone-Patellar Tendon-Bone Autograft

Abstract: When overlapping or discordant systematic reviews are encountered, each review must be appraised on the basis of its methodological quality before it can be used to guide clinical decision-making or policy making. The currently available best evidence, derived from a methodologically sound meta-analysis, suggests that hamstring tendon autografts are superior for preventing anterior knee pain, and there is limited evidence that bone-patellar tendon-bone autografts provide better stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 26 publications
0
58
0
2
Order By: Relevance
“…In fact, mortality (5,7,12), MI (7,11,12), and stroke (2, 7, 10) fell into the same pattern as the composite outcome in only 3 of 16 clusters each.…”
Section: Concordance Of Meta-analytic Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, mortality (5,7,12), MI (7,11,12), and stroke (2, 7, 10) fell into the same pattern as the composite outcome in only 3 of 16 clusters each.…”
Section: Concordance Of Meta-analytic Resultsmentioning
confidence: 90%
“…We used the checklist by Oxman and Guyatt [4] to assess the quality of included SRs. When a previous review was cited, we abstracted the authors' rationale for repeating the review, if reported [12].…”
Section: Methodsmentioning
confidence: 99%
“…However, since the publication of those reviews, additional data have been published, and the discussion about the indications for operative treatment is ongoing 13,18 . Even though the present meta-analysis has substantial overlap with previous ones, we believe that it adds methodological quality and incorporates recently published data to provide the best currently available evidence to support clinical decision-making 19 .…”
mentioning
confidence: 99%
“…If this date was not available, we used its acceptance for publication date, publication date or the date of the most recent citation in the references. When a previous review was cited, we abstracted the authors' rationale for repeating the review, if reported [9]. Phase 6: detecting discordant reviews among multiple reviews (Jadad algorithm)…”
Section: Phase 5: Author's Rationale For Repeating the Reviewmentioning
confidence: 99%
“…The algorithm helps readers to evaluate possible sources of discordance among reviews [9]. The algorithm first step involves overlapping of (a) the clinical question (population of patients, interventions, control and outcomes), which characterizes our clusters.…”
Section: Assessment Of Conclusionmentioning
confidence: 99%